Vector competence of biting midges and mosquitoes for Shuni virus. - Tim W R Möhlmann; Judith Oymans; Paul J Wichgers Schreur; Constantianus J M Koenraadt; Jeroen Kortekaas; Chantal B F Vogels (Public Library of Science (PLoS), 2019)
Background Shuni virus (SHUV) is an orthobunyavirus that belongs to the Simbu serogroup. SHUV was isolated from diverse species of domesticated animals and wildlife, and is associated with neurological disease, abortions, and congenital malformations. Recently, SHUV caused outbreaks among ruminants in Israel, representing the first incursions outside the African continent. The isolation of SHUV from a febrile child in Nigeria and seroprevalence among veterinarians in South Africa suggests that the virus may have zoonotic potential as well. The high pathogenicity, extremely broad tropism, potential transmission via both biting midges and mosquitoes, and zoonotic features of SHUV require further investigation. This is important to accurately determine the risk for animal and human health, and to facilitate preparations for potential epidemics. To gain first insight into the potential involvement of biting midges and mosquitoes in SHUV transmission we have investigated the ability of SHUV to infect two species of laboratory-colonised biting midges and two species of mosquitoes. Methodology/principal findings Culicoides nubeculosus, C. sonorensis, Culex pipiens pipiens, and Aedes aegypti were orally exposed to SHUV by providing an infectious blood meal. Biting midges showed high infection rates of approximately 40%-60%, whereas infection rates of mosquitoes were only 0-2%. Moreover, successful dissemination in both species of biting midges and no evidence for transmission by orally exposed mosquitoes was found. Conclusions/significance The results of this study suggest that different species of Culicoides midges are efficient in SHUV transmission, while the involvement of mosquitoes has not been supported.